2016
DOI: 10.1186/s12893-016-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pneumatosis intestinalis (PI) and portal venous gas (PVG) may indicate bowel necrosis: a 52-case study

Abstract: BackgroundThe significance of pneumatosis intestinalis (PI) and portal venous gas (PVG) is controversial. This retrospective study evaluated the risk factors for bowel necrosis in patients with PI and/or PVG.MethodsBetween 2002 and 2015, 52 patients were diagnosed with PI and/or PVG and were included in this study. The patients were classified according to the presence or absence of bowel necrosis in surgical findings or at autopsy. Patient characteristics and clinical findings related to bowel necrosis were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
2
19
1
5
Order By: Relevance
“…We demonstrated that only the WCC, BE and lactate levels varied significantly between the aetiology groups. This is in contrast to other studies which have previously demonstrated that CRP, creatinine and lactate different in ischaemic aetiologies . These findings, however, have limited clinical application due to the large variation and overlap in results between groups.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…We demonstrated that only the WCC, BE and lactate levels varied significantly between the aetiology groups. This is in contrast to other studies which have previously demonstrated that CRP, creatinine and lactate different in ischaemic aetiologies . These findings, however, have limited clinical application due to the large variation and overlap in results between groups.…”
Section: Discussioncontrasting
confidence: 93%
“…Even if a management flowchart or algorithm is provided by some studies, this is often based of small numbers of cases or limited literature review . Previous studies have grouped both PVG and pneumatosis intestinalis to increase numbers . However, we believe that this in inappropriate given the different pathophysiology and aetiology of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who present with obscure symptoms, because of their highly advanced age or impaired consciousness, for example, might bene t from measurement of these variables at diagnosis. These variables, other than NLR, have been already reported to be candidate predictors of bowel ischemia in patients with HPVG [16,[22][23][24][25][26][27]. However, no previous reports have described an association between high NLR and bowel ischemia in HPVG patients, although some researchers have suggested that NLR might be useful for the identi cation of, and assessment of the severity of, acute mesenteric ischemia [28].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with abdominal radiographs in predicting NEC, studies showed that they can depict bowel distension, to some extent bowelwall thickness, pneumatosis intestinalis, portal venous air and free abdominal air which ultrasound could easily depict as well. More importantly, abdominal ultrasound provides important additional information regarding viability of bowel wall viability and free fluid, which might aid in diagnosis and management of NEC [44,45]. With color Doppler specific suspicious loops of bowel can be interrogated to reveal if they are perfused or not which enables the identification of non-viable bowel with a high degree of certainty.…”
Section: Bowelmentioning
confidence: 99%